The Impact of task and technology characteristics on cost estimation performance in construction projects: A regression analysis - Mohammad Waffy, Fazil; Puteri Fadzline, Muhamad Tamyez; Lee, Chia Kuang (Akademia Baru, 2023)
Accurate cost estimation is crucial for the success of construction projects worldwide. However, many projects encounter failures due to challenges in this area. Existing research has primarily focused on developing and comparing cost estimation methods, as well as identifying factors and best practices for improving cost estimation performance. Yet, only a limited number of studies have explored deeply into the relationship between these factors and cost estimation performance. This study aims to address this gap by investigating how task characteristics and cost estimation method characteristics affect cost estimation performance from the perspective of cost estimators. Data were collected from cost estimators in construction projects and subsequently analyzed using multiple regression analysis. The results demonstrate that task interdependence and the cost estimation method characteristics significantly impact the cost estimation performance. This study provides novel insights regarding the significance of these method characteristics and sheds light on which task characteristics influence the cost estimation performance. It also provides the importance of fostering a positive organizational culture to mitigate the adverse effects of task interdependence on cost estimation performance. Furthermore, this study recommends further exploration of the interaction between task and cost estimation method characteristics through task-technology fit theory or moderator analysis.